Association between the clinical severity of oral lichen planus and anti-TPO level in thyroid patients - Milad ALIKHANI; Parichehr GHALAIANI; Elham ASKARIYAN; Zahra Ahmadi KHUNSARAKI; Atefeh TAVANGAR; Aliasghar NADERI
Abstract This study considered a possible relationship between the severity of oral lichen planus (OLP), serum anti-TPO autoantibodies (TPOAb) titer and thyroid disease in OLP patients. Forty-six OLP patients with positive TPOAb results (> 35 IU/ml) who had also been diagnosed with thyroid disease were included in the study group. The control group consisted of 46OLP patients with no thyroid disease. The study and control groups (92) were divided to two subgroups of erosive OLP (EOLP) and non-erosive OLP (NEOLP). Serum TPOAb levels and IL-8 (to measure OLP severity) were evaluated using the independent t-test, chi-square and conditional logistic regression analysis (α = 0.05). A significant positive correlation was found between serum IL-8 and TPOAb levels in the study group (r = 0.783; p = 0.001). The positive blood levels of TPOAb were significantly associated with an increased risk of EOLP (OR = 4.02 at 95%CI; 1.21-13.4; p = 0.023). It is possible to used positive serum TPOAb levels in patients with OLP as in indicator of possible undetected thyroid disorders in those patients. Because erosive OLP has been associated with TPOAb in thyroid patients, it may be useful to determine TPOAb levels of such patients to diagnose a possible undetected thyroid disorders and follow-up for malignancy.